Rousseau and Becker on the problem of recognition: a comparative analysis - Bick-Hardie, James (Journal of Theoretical and Philosophical Criminology, 2024)
This article identifies the main parallels that exist between Rousseau and Becker on recognition. Rousseau and Becker argue that people are motivated by a desire to achieve recognition from others. Their work explains how the craving for recognition contributes to the common good, but they also address the serious problems that can arise. Whilst the human striving for recognition is often beneficial for society, their work describes the devastating consequences that accompany this existential desire. The article begins by outlining their work on amour-propre (Rousseau) and heroism (Becker) before tracing the similarities and differences between their work in relation to restricting destructive forms of behaviour. The overall aim of this comparative analysis is to highlight the connections that exist between Rousseau and Becker and to show how Becker's insights concerning mortality awareness and heroism provide an important contribution to contemporary scholarship on self-worth and recognition.